The Determinant of Product Advantage, Customer Experience and Trust on the Reputation of Bank Syariah Indonesia Post-Merger at Surakarta City - Agung Abdullah (Falah: Jurnal Ekonomi Syariah, 2022)
This study aims to determine the impact of product advantage, customer experience and trust on the reputation of Bank Syariah Indonesia post-merger at Surakarta City. This research was quantitative with data analysis techniques using multiple linear regression. The sampling technique in this study was purposive sampling with certain criteria. The respondent in this study were 100 customers of Bank Syariah Indonesia at Surakarta City. The result found that product advantage has a positive and significant effect on company reputation, customer experience has a positive and significant effect on company reputation and trust has a positive and significant effect on Bank Syariah Indonesia reputation. This study provided a useful contribution to enrich the discourse on the impact of Islamic bank mergers, especially on the reputation of Islamic banks after the merger. This reputation will increase an optimistic sentiment for Bank Syariah Indonesia even in the negative growth of economic caused by the pandemic Covid-19.